Intensitas Penggunaan Gadget terhadap Self Esteem - Fareesah Koowa; Arifin Nur Budiono; Sri Prawita (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2020)
Self esteem is self-evaluation. This research was conducted to see the influence of the use of gadgets on student self esteem. Methods of study used quantitive methods and simple correlates. The purpose of this correlation study was conducted to determine the influence between the research objectives of correlation is done to know the influence between the free variable (independent variable) namely the intensity of use of gadgets and bound variables (dependent variable) i.e. self esteem. Research location at SMP 01 Islam Jember. Data collection is done by means of interviews, polls and documents. Based on statistical tests using the Pearson Product Moment test obtained a R value of 0.4022 with a range of correlation coefficients ranging between-1, 0 and 1 It can be concluded that there is a moderate relationship. From the result of the calculation by using T test, obtained t count by 10.07433 thereby hypothesis (ha) that said that there is influence of the intensity of use of gadgets against self esteem Students class VII SMP Islam Jember Received and hypotheses (HO) Be dipelling.  Keywords: Intensity Gadget, Self Esteem